A new, enigmatic species of black-eyed gecko (Reptilia: Diplodactylidae: Mokopirirakau) from North Otago, New Zealand - Knox, Carey; Hitchmough, Rodney A.; Nielsen, Stuart V.; Jewell, Tony; Bell, Trent (Zootaxa, 2021)
The New Zealand endemic gecko genus, Mokopirirakau, is notable for its ecology, with some species inhabiting extreme alpine environments, as well as for the large number of geographically circumscribed, species-level lineages awaiting formal description. In, 2018, a population superficially similar in colour and morphology to the black-eyed gecko (M. kahutarae) was discovered in alpine greywacke rock outcrops in the Oteake Conservation Park, North Otago, 400 km south of the nearest M. kahutarae populations in the upper South Island. Genetic and morphological data indicate that this population is distinct, sister to a clade comprising M. granulatus and M. kahutarae. It can be distinguished from all but one Mokopirirakau species by colour pattern, and from M. kahutarae by smaller adult body size, eye and supraciliary characters, mouth and throat colour, ventral scale row count, tail length, toe shape, and lamellar count. Using an integrated taxonomic approach, we here formally describe this form as a new species, M. galaxias sp. nov., as well as discuss its ecology, likely distribution (particularly with respect to M. kahutarae), and potential conservation issues and requirements. Mokopirirakau galaxias sp. nov. should be considered “Threatened—Nationally Endangered” (qualifiers Data Poor) in the New Zealand Threat Classification System due to the low abundance and restricted known distribution, with potential threats from invasive predatory mammals and climate change. It should be considered Data Deficient in the IUCN Red List system.